Acute Lupus Pneumonitis Mimicking Pneumonia: Diagnostic Challenges and Management in A 40-Year-old Sle Patient - Made Dwi Wulandari, Ni; Dyah Widyaningsih, Putu; Komang Rusgi Yandi, I (Devotion : Journal of Research and Community Service, 2026)
Acute Lupus Pneumonitis (ALP) is a rare pulmonary complication of Systemic Lupus Erythematosus (SLE) with a mortality rate of up to 50%. The greatest challenge for clinicians is identifying this condition amid symptoms that closely resemble severe pneumonia or pulmonary edema, to ensure appropriate management. This case report aims to describe the diagnostic challenges, clinical presentation, and therapeutic response of ALP in an SLE patient presenting with acute respiratory failure, and to emphasize the importance of early high-dose corticosteroid therapy. A 40-year-old woman with SLE presented with progressive dyspnea, cough, and fever lasting one week. She rapidly developed severe hypoxemic respiratory failure, with an oxygen saturation of 58% on room air and a PaO₂/FiO₂ ratio of 42 mmHg, consistent with severe ARDS. Chest X-ray revealed extensive bilateral infiltrates with a normal cardiac silhouette. Laboratory findings showed thrombocytopenia and lymphopenia, suggesting active lupus disease activity, while negative culture results excluded bacterial infection. The patient received High-Flow Nasal Cannula (HFNC) therapy and immediate pulse-dose methylprednisolone. Within 24 hours, oxygenation improved markedly (PaO₂/FiO₂ ratio 162 mmHg). After 10 days, she achieved full recovery and was discharged without oxygen supplementation. Acute Lupus Pneumonitis should be suspected in SLE patients presenting with severe hypoxemia and bilateral infiltrates after excluding cardiogenic and infectious causes. Early initiation of high-dose corticosteroids is crucial to reducing mortality. A systematic diagnostic approach combined with prompt immunosuppressive therapy is essential for achieving optimal outcomes.